Respostas
respondido por:
1
Resposta:
√6/3 (opção: A)
Explicação passo-a-passo:
.
. (3/2)^-1 ÷ (2/3)^1/2 = (2/3)¹ ÷ (2/3)^1/2
. = (2/3)^(1-1/2)
, = (2/3)^1/2
. = √(2/3)
. = √2 / √3
. = √2 . √3 / √3 . √3
. = √(2 . 3) / √3²
. = √6/3
.
(Espero ter colaborado)
respondido por:
1
Resposta:
Opção a: √6/3
Explicação passo-a-passo:
(3/2)⁻¹ ÷ (2/3)¹/²
(3/2)⁻¹ ÷ (3/2)⁻¹/²
(3/2)⁻¹/²
(2/3)¹/²
√2/3
√2/√3
√6/3
Espero ter ajudado.
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás